Technology Options for the Built Environment in Kenya: Dye- Sensitized and Amorphous Silicon Photovoltaics for Application in NZE Buildings - Otakwa, R.; Othieno, H.; Awange, Joseph; Oduor, A. (Bentham Science Publishers Ltd., 2017)
Background The performance of a Dye-Sensitized Solar Module (DSSM) has been investigated under different outdoor air mass (AM), irradiance intensity and temperature conditions in Wajir, Kitui, Vihiga and Kajiado Counties in Kenya. Methods The performance was thereafter compared with that of Amorphous Silicon (a-Si) devices undertaken under similar weather conditions in Nigeria. The DSSM’s good response to short wavelength radiation made it perform better at increased AM values than what has been reported of a-Si PV modules. Results Studies on a-Si showed that their performance favors low AM conditions. The DSSM generally performed better than what is reported of a-Si, based on irradiance and temperature dependence. Nonetheless, a-Si devices performed better at higher irradiance intensities. These results show that Dye-Sensitized and a-Si technologies complement each others’ performance when subjected to the outdoor field AM, irradiance and temperature conditions. Conclusion These findings can be applied in PV sizing, especially for application in Building Integrated Photovoltaics (BIPV) in the tropics.